Inhibitory receptor signals suppress ligation-induced recruitment of NKG2D to GM1-rich membrane domains at the human NK cell immune synapse. - Endt, J; McCann, F; Almeida, C; Urlaub, D; Leung, R; Pende, D; Davis, D; Watzl, C (2007)
NKG2D is an activating receptor expressed on all human NK cells and a subset of T cells. In cytolytic conjugates between NK cells and target cells expressing its ligand MHC class I chain-related gene A, NKG2D accumulates at the immunological synapse with GM1-rich microdomains. Furthermore, NKG2D is specifically recruited to detergent-resistant membrane fractions upon ligation. However, in the presence of a strong inhibitory stimulus, NKG2D-mediated cytotoxicity can be intercepted, and recruitment of NKG2D to the immunological synapse and detergent-resistant membrane fractions is blocked. Also, downstream phosphorylation of Vav-1 triggered by NKG2D ligation is circumvented by coengaging inhibitory receptors. Thus, we propose that one way in which inhibitory signaling can control NKG2D-mediated activation is by blocking its recruitment to GM1-rich membrane domains. The accumulation of activating NK cell receptors in GM1-rich microdomains may provide the necessary platform from which stimulatory signals can proceed.